Normative Audit Control for On-Line/Real-Time Systems: A Feasibility Study. - Baker, C. Richard (The Accounting Review, 1975)
Reviews the book "Normative Audit Control for On-Line/Real-Time Systems: A Feasibility Study," by Maxwell E. Aiken, Kevin G. Hulme and Phillip J. Grouse.